Indicators of Desertification and its Impact on the Degradation of Agricultural Lands: A study of the Geography of Gadaref State - Sulieman, Salwa Hassan Ahmed (Journal of agricultural, environmental and veterinary sciences, 2023)
The present study dealt with the indicators of desertification in the state of Gedaref and its impact on agricultural, economic and social production, indicating the dimensions and effects on the people of the state in the present and the future, and identifying the most important natural and human factors that led to the exacerbation of the problems of the phenomenon of desertification. The importance of the current study stems from the fact that the phenomenon of desertification has become a threat to plant and animal life in general and that the spread of this phenomenon leads to a lack of natural vegetation as well as agricultural production and encroachment on forests for housing, overgrazing and cutting wood. Thus, the phenomenon of desertification threatens human, economic and environmental life in the study area. The objectives of the study include defining desertification and its related factors, in addition to exploring the indicators of desertification in the state of Gedaref and highlighting the seriousness of the phenomenon and how to help in treating it according to the regional and international standards used to deal with the problems of desertification and drawing the attention of the competent authorities to address the problem in the state. The study obtained several realistic results, the most important of which is that there are several indicators for the relevant administrative authorities to consider as natural and human factors that led to an increase in the severity of desertification in the state of Gedaref and the importance of the state as the largest source of food security in Sudan that must be circumvented to avoid its severity in the present and its aggravation in the future. The results also showed that desertification is a natural and human phenomenon that arises as a result of natural and human factors and lead to negative economic and social results in the lives of peoples, in addition to explaining the reality of desertification in the region and highlighting its seriousness and methods of treatment and combating this phenomenon.